Diffusion Tensor Imaging of Neural Tissue Organization: Correlations between Radiologic and Histologic Parameters. Issue 5 (October 2013) - Wei, Petert; Leong, Dalun; Calabrese, Evan; White, Leonard; Pierce, Theodore; Platt, Simon; Provenzale, James
This study examined the relationship between histological variables and diffusion tensor imaging (DTI) values in a normal canine brain. We hypothesized that radial diffusivity (RD) would correlate with myelin density and fractional anisotropy (FA) would correlate with white matter fiber coherence. We acquired DTI maps of a normal canine brain post mortem on a 7T MR scanner (TR = 100 ms, TE = 18.1 ms, NEX = 1, width [d] = 4 ms, separation [D] = 8.9 ms, gradient amplitude = 600 mT/m, b=1, 565 s/mm 2 ) and generated maps of FA, RD, and axial diffusivity. The brain was subsequently sectioned and stained for myelin with gold chloride, which also allowed for measurement of fiber coherence. DTI metrics were then directly compared with the optical density of the myelin stain and the coherence of stained fibers. Multivariate linear regression demonstrated that RD, but not FA, significantly correlated with both myelin stain intensity (p = 0.031) and fiber coherence (p = 0.035). The Pearson correlation coefficient between these two histological variables and FA was 0.122; and was 0.607 for the histological variables and RD. We found that RD significantly correlated with both optical density of myelinated fibers and fiber coherence, but FA correlated with neither histological finding. Factors other than degree of myelination and fiber coherence should be considered to fully account for regional variation in FA.